Effect of Coconut Fiber Wall Panels on Humidity Conditions in a Tropical House - Wila Prakasita Scotiswara Supomo; I Gusti Ngurah Antaryama; FX Teddy Badai Samodra (DIMENSI (Journal of Architecture and Built Environment), 2024)
Houses in warm and humid tropical regions, like Indonesia, often experience uncomfortable conditions due to high temperatures aggravated by high humidity. With its adsorptive characteristics, natural coconut fiber can be utilized as wall panels and assigned to regulate house humidity levels. Research focusing on investigating the adsorptive capability of the natural coconut fiber in controlling humidity is widely available, but that specifically examines the effect of the surface area of the material on air humidity conditions in humid tropical extant houses is still limited. A field experiment was conducted in a small Surabaya house. The study analyzes the impact of coconut fiber (CF) wall panels on humidity conditions in each house room and the optimal surface area of the wall panels. CF wall panels were found to reduce the indoor relative humidity (RH) significantly. The optimal surface area varied depending on room characteristics. The optimal surface area of the wall panels for the living room is six (6) m² with a 28% RH reduction, for the bedroom is six (6) m² with a 27% reduction, and for the kitchen is five (5) m² with a 27% reduction.